A New Look at Exchange Rate Volatility and Trade Flows - Clark, Peter (Occasional Papers; Occasional Paper, 2004)
The effect of exchange rate volatility on trade flows was examined by a 1984 IMF study on G-7 countries. Over the past two decades, many developments in the world economy, such as the currency crises in the 1990s and increasing cross-border capital flows, may have exacerbated exchange rate volatility, while others, such as a deepening of the market in foreign exchange hedging instruments, may have reduced the impact of volatility on trade flows. Using recent advances in the economic theories on trade and in statistical methodologies, this paper revisits this important issue by taking into account these new developments and examining their effects on developing and transition economies, as well as on developed countries.